2013
DOI: 10.1158/1055-9965.epi-12-1174
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Genetic Testing, Counseling, and Adherence to Skin Cancer Prevention and Detection Behaviors

Abstract: Background Little is known about the impact of knowledge of CDKN2A and MC1R genotype on melanoma prevention behaviors like sun avoidance and skin examination in the context of familial melanoma. Methods 73 adults with a family history of melanoma were randomly assigned to be offered individualized CDKN2A and MC1R genotyping results in the context of a genetic counseling session, or the standard practice of not being offered counseling or disclosure of genotyping results. Mixed effects or longitudinal logisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 21 publications
4
46
0
Order By: Relevance
“…A key issue has been whether genetic testing is necessary, as test results do not alter management recommendations concerning sun-protection and skin screening for members of melanoma-prone families. Improvements in sun-protection and screening behavior following receipt of genetic test results have been reported up to two years later by unaffected carriers in prior studies (Aspinwall, Taber, Leaf, et al, 2013, 2014; see also Glanz et al 2013; Kasparian et al, 2009), but because all of these participants received both genetic counseling and test results, these benefits cannot be uniquely attributed to receipt of a positive genetic test result. The benefits of genetic test reporting compared to family history-based counseling identified in the present study – including greater understanding of risk and enhanced acceptance of risk and prevention recommendations – may ultimately lead to increased prevention and detection behaviors.…”
Section: Discussionmentioning
confidence: 91%
“…A key issue has been whether genetic testing is necessary, as test results do not alter management recommendations concerning sun-protection and skin screening for members of melanoma-prone families. Improvements in sun-protection and screening behavior following receipt of genetic test results have been reported up to two years later by unaffected carriers in prior studies (Aspinwall, Taber, Leaf, et al, 2013, 2014; see also Glanz et al 2013; Kasparian et al, 2009), but because all of these participants received both genetic counseling and test results, these benefits cannot be uniquely attributed to receipt of a positive genetic test result. The benefits of genetic test reporting compared to family history-based counseling identified in the present study – including greater understanding of risk and enhanced acceptance of risk and prevention recommendations – may ultimately lead to increased prevention and detection behaviors.…”
Section: Discussionmentioning
confidence: 91%
“…34 40 One study communicated the risks of melanoma. 31 One study communicated the risks of colorectal cancer. 49 Three studies communicated the risk of type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…31 The comparison was between DNA based risk estimates versus no risk estimates. The standardised mean difference was 0.43 (95% confidence interval −0.03 to 0.90, P=0.07), suggesting no effect of DNA based risk communication ( fig 3).…”
Section: Sun Protection Behavioursmentioning
confidence: 99%
“…Melanoma genetic testing is just beginning to transition to routine clinical use (Leachman et al, 2009), though researchers and clinicians have previously questioned its clinical utility. Concerns about testing have included the low percentage of high-risk melanoma families that could be attributed to p16 mutations, variability of penetrance estimates, the potential for individuals testing negative for a familial mutation to still have increased risk due to the presence of other factors in the family (e.g., phenotype, sun exposure), and the lack of empirical data to determine whether benefits outweigh costs (Kefford et al, 2002; Kefford & Mann, 2003), Recent data, however, support a role for melanoma genetic testing in promoting improved screening among unaffected carrier family members (Aspinwall et al, 2008, 2013b; Glanz et al, 2013; Kasparian et al, 2009). In particular, unaffected carriers in our study of two extended p16 kindreds reported improvements in the thoroughness of skin self-examinations and improved adherence to annual total body skin examinations 2 years following melanoma genetic testing (Aspinwall et al, 2013b).…”
mentioning
confidence: 99%